Factor structure of the Self-Regulation Questionnaire among adult learners from Poland, Serbia, Slovakia, and the Czech Republic - Jitka Vaculíková; Ilona Kočvarová; Jan Kalenda; Zuzana Neupauer; Marija Cvijetić Vukčević; Anna Włoch (Psicologia: Reflexão e Crítica, 2022)
Abstract Background One of the most significant human qualities is the ability to develop, implement, and flexibly maintain planned behaviour in order to achieve one’s goals. Self-regulation has become a relatively well-researched area in the field of psychology and pedagogy. However, empirically valid and reliable instrument is still missing across European context. The primary goal of this research was to analyze the psychometric properties of the Czech version of the Self-Regulation Questionnaire (SRQ-CZ) among adult learners from Poland, Serbia, Slovakia, and the Czech Republic. Objective The aim of the present study was to examine the factor structure and psychometric properties of the SRQ-CZ validated in the Czech educational context in a multi-cultural sample. Methods A total of 1711 adult learners from European countries including Poland, Serbia, Slovakia, and the Czech Republic completed the SRQ-CZ. The first step to reviewing the validity of the SRQ-CZ included testing face validity. Furthermore, exploratory factor analysis (EFA) was performed on half the sample and confirmatory factor analysis (CFA) on the other half. Measurement invariance was conducted across gender, age, and country followed by the evaluation of the reliability of the final instrument. Results EFA showed that a three-factor structure best fit the data. The originally proposed Impulse Control and Self-Direction are merged into one distinct factor, while Decision Making and Goal Orientation comprise the other two. Goodness-of-fit statistics yielded from CFA showed a good fit for the model, introducing a reliable and measurement invariant instrument. Conclusion The present study used a diverse multi-cultural sample to explore the factorial structure and psychometric properties of the SRQ-CZ. A three-factor model was obtained as the result of the exploratory and confirmatory factor analyses. Further analysis aiming at measurement invariance, comparing the sample according to gender, age, and country, led to satisfactory results. The only exception was a lack of model fit in the case of Serbia. Although further psychometric evaluation of the SRQ-CZ is still needed, the presented results constitute significant findings, confirming instrument validity and utility as a measure of generalized self-regulation capacity across adult learners in European educational context.